تأثير طرق الربط لوصلات المنشآت المعدنية على الأداء الافضل باستخدام طريقة العناصر المنتهية - محمد غانم زهرة; تمام جميل سلوم; مهند فائز نصره (Tishreen University, 2019)
يقدم هذا البحث دراسة بمساعدة طريقة العناصر المنتهية وباستخدام برنامج CATIA V5 لأنواع الوصلات المستخدمة في المنشآت المعدنية حيث تمت دراسة عدة أنواع  من الوصلات بأساليب ربط مختلفة عبر تصميم هذه الوصلات و نمذجتها وإجراء محاكاة لمنشأة افتراضية قائمة على هذا النوع من الوصلات. الوصلات التي تمت دراستها في هذا البحث (وصلة بين مقطعينI ملحومتين من الأعلى و الأسفل , وصلة أخرى بين مقطعين I ملحومتين من الأعلى و الأسفل و من الجوانب , وصلات من مقطعي I موصولين مع بعض باستخدام صفائح ملحومة من الجهة العلوية و السفلية , وصلات صفائح مثبتة ببراغي , وصلات مثبتة ببراغي ولحام , وصلات صفائح مثبتة ببراغي من الأعلى الأسفل و من الجوانب , وصلات عارضة وعمود وصفيحة جبهية باستخدام براغي) حيث تم في كل حالة حساب الإجهادات الأعظمية الناشئة و الانتقالات  وكذلك حساب الإجهادات المركزة في الوصلة ( علوية و سفلية و جانبية) وتمت المقارنة بين جميع القيم ورسم المخططات بين هذه الحالات. وبعد ذلك تمت دراسة تأثير عدد البراغي على الإجهادات و الانتقالات ومقارنتها بحالات وجود اللحام للوصل للحالة الافضل وكذلك درس تأثير عدد و سماكة أعصاب التقوية على الإجهادات و الانتقالات الناشئة في وصلات عارضة عمود مع صفيحة جبهية. This research presents a study using the finite element method and using the CATIA V5 program for the types of joints used in metal structures. Several types of joints were studied using different linking methods through the design and modeling of these links and simulation of a virtual facility based on this type of connection. The links studied in this study (a link between two sections I welded from the top and bottom, and another link between the two sections I welded from the top and bottom and from the sides, joints of the I segments are connected with some using welded plates from the top and bottom, Screws, bolts and bolts fastened joints, threaded joints with bolts from the top and bottom, couplings, column and front plate using bolts). In each case, the resulting maximum stresses and transitions were calculated as well as the concentration of the concentric stresses in the link (Top, bottom and side) All values ​​were compared and plotted Khttat between these cases. The effect of the number of bolts on the stresses and transitions was studied and compared with the presence of welding to connect to the best case. Also, the effect of the number and thickness of the reinforcing nerves on the stresses and transitions in the couplings of a column with a front plate was studied.